Assessment of the state of nutritionality and method of food of children of furnishing to basic and gynal schools - Katarzyna Sawicka; Agnieszka Wawryniuk; Robert Łuczyk; Ewa Krzyżanowska; Natalia Szubiela; Marta Łuczyk; Jadwiga Daniluk (Kazimierz Wielki University, 2017)
Admission. The school term in the child's life is the stage at which the eating habits begin to develop. Consistent in childhood and adolescence, nutritional errors are transposed into adult life and can result in many nutritional-dependent diseases. Aim of the job. Assessment of the nutritional status and nutrition of children attending primary and lower secondary schools Material and methods. The study covered 220 primary and lower secondary school students of both sexes aged 7-16. The study included: assessment of the nutritional status of primary and lower secondary school children on the basis of their own questionnaire survey and nutritional assessment based on calculated BMI (based on BMI centimeters based on age and sex). Results. Over 60% of primary school pupils and 79% of secondary school pupils are observed to have a good nutritional status. Nutritional disorders are more likely to affect children attending primary school, 17.3% of whom are overweight, 10% are obese, and 12.7% are deficient in body weight. Both groups of students eat: insufficient quantities of high fiber foods, insufficient amount of milk and milk products, vegetables and fruits, and insufficient quantity of fish. In addition, children attending primary and lower secondary schools consume excessive amounts of fried meat and sugar.